2015
DOI: 10.1177/1758834014567117
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase (ALK) gene alteration in signet ring cell carcinoma of the gastrointestinal tract

Abstract: Objectives: ALK-EML4 translocation is an established driver aberration in non-small cell lung cancer (NSCLC), with reported predilection for cases with signet ring histology. We assessed the presence of anaplastic lymphoma kinase (ALK) gene rearrangements in signet ring cancers arising in the stomach and colon. Methods: Histologically confirmed cases of signet ring adenocarcinoma of the stomach or the colon were identified. The presence of the classic ALK and EML4 fusion gene was initially determined by fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Moreover, Ferreri et al (2012) reported in their study on ALCL that ALK + ALCL cases were characterized by five distinctive patterns: young age, male predominance, advanced stage, systemic symptoms, and extranodal involvement. Moreover, increased proportion of signet ring cell gastric carcinoma cases with ALK + immunostaining in this study was in agreement with other studies, in which Alese et al (2015) found increased ALK gene rearrangement in signet ring cell carcinoma of gastrointestinal tract. Moreover, Popat et al (2012) observed that ALK rearranged lung adenocarcinomas had the signet ring morphology, suggesting the biologic function of ALK rearrangement in signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Moreover, Ferreri et al (2012) reported in their study on ALCL that ALK + ALCL cases were characterized by five distinctive patterns: young age, male predominance, advanced stage, systemic symptoms, and extranodal involvement. Moreover, increased proportion of signet ring cell gastric carcinoma cases with ALK + immunostaining in this study was in agreement with other studies, in which Alese et al (2015) found increased ALK gene rearrangement in signet ring cell carcinoma of gastrointestinal tract. Moreover, Popat et al (2012) observed that ALK rearranged lung adenocarcinomas had the signet ring morphology, suggesting the biologic function of ALK rearrangement in signet ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 95%
“…In our study, ALK expression was found in only 11.8% of gastric carcinoma cases. Similarly, a low incidence of ALK gene rearrangement in gastrointestinal tumors was reported by Alese et al (2015), who found that ALK gene rearrangement detected with immunohistochemistry is rare in gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 79%
“…ALK and ROS1 rearrangements (enlisted in Table 1a) rarely have been also identified in mCRC using technologies based on fluorescence in situ hybridization (FISH) [61], exon array profiling [62], and next generation sequencing (NGS) [14,33] performed on archival tumor specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the gene fusion mutations in gastric or signet ring adenocarcinoma are few, which may be related to the usual use of methods other than NGS in the past. For example, in 42 cases of signet ring cell carcinoma of the gastrointestinal tract, two different ALK antibody based IHC did not detect the “possibly positive” cases with ALK translocation detected by FISH ( 6 ). With the application of NGS technology and other genomic technologies, GC is currently being studied and typed in more detail at the molecular level.…”
Section: Discussionmentioning
confidence: 99%